USOS DE ἀνά EN HERÓDOTO Y TUCÍDIDES - Martínez Valladares, María Angeles (Myrtia, 2002)
It’s a exhaustive study about the preposition ἀνά in the work of Herodot and Thucydidis. The index of frecuency of ἀνά in the “Historiae” of Herodot is high, 66 phrases. He is a ionic writer. Thucydidis only uses ἀνά in 2 occasions. The attic historian employs the preposition κατά so that express the same circumstance as ἀνά. In the attic prose appears rarely ἀνά. We can see κατά with similar value. Herodot uses ἀνά with accusative case in order to indicate circumstance of “place”, “time” and “notion”. In the two phrases of Thucydidis the meaning of ἀνά is “local”.